Qiling decoction enhances the anti-tumor activity of abiraterone acetate by up-regulating miR-143 expression in abiraterone acetate-resistant prostate cancer cells - Chen, Lizhi; Cao, Hongwen; Sun, Peng; Feng, Yigeng; Chen, Lei; Gao, Renjie (Frontiers in Medicine, 2025)
IntroductionAbiraterone acetate is a key therapeutic agent for castration-resistant prostate cancer (CRPC), but the cancer resistance limits its long-term efficacy. While several mechanisms of abiraterone acetate resistance have been proposed, the role of microRNAs (miRNAs) in this process remains incompletely understood. Here the aim of the study was to investigate miR-143 as a potential tumor suppressor in prostate cancer, and elucidate its involvement in abiraterone acetate resistance. Additionally, Qiling decoction (QLD), a traditional Chinese medicine formulation, was tested for its ability to restore miR-143 expression and enhance abiraterone efficacy.MethodsAbiraterone acetate-resistant prostate cancer (PC) cell lines, PC3-AbiR and DU145-AbiR, were established through long-term abiraterone exposure. The expression of miR-143 was analyzed using qRT-PCR, and its effects on the JNK/p-Bcl2-Beclin1 signaling axis were examined via Western blot and co-immunoprecipitation assays. Functional experiments, including CCK-8 assays, were carried out to evaluate how miR-143 modulation affects abiraterone acetate sensitivity.ResultsmiR-143 expression was significantly downregulated in abiraterone acetate-resistant PC cells. Downregulation of miR-143 was shown to be linked with increased phosphorylation of JNK and p-Bcl2, along with elevated expression of Beclin1, indicating activation of the JNK/p-Bcl2-Beclin1 signaling axis. Functional studies revealed that miR-143 inhibition promoted cell survival and autophagy, while its overexpression restored abiraterone acetate sensitivity. Treatment with QLD upregulated miR-143 expression, suppressed JNK/p-Bcl2-Beclin1 signaling, and enhanced abiraterone acetate-induced cytotoxicity. Inhibition of miR-143 abolished the effects of QLD, confirming its central role in mediating abiraterone acetate resistance. These findings demonstrate that miR-143 downregulation contributes to abiraterone acetate resistance in prostate cancer by activating the JNK/p-Bcl2-Beclin1 signaling axis and promoting autophagy.ConclusionRestoration of miR-143 expression through QLD treatment enhances abiraterone acetate sensitivity, suggesting a potential therapeutic strategy for overcoming drug resistance in CRPC.